Extracorporeal light-chain elimination in myeloma with simple medium cutoff membrane hemodialysis: a retrospective cohort study - Schaaf, Christian W.; Braunisch, Matthias C.; Holzmann-Littig, Christopher; Pfister, Frederick; Hannemann, Liya; Hausinger, Renate I.; Verbeek, Mareike; Schmaderer, Christoph; Renders, Lutz; Heemann, Uwe; Küchle, Claudius (Frontiers in Oncology, 2023)
We determined the efficacy of free light chain (FLC) removal by regular dialysis equipment (high-flux filtration) with Medium Cut-Off (MCO) membrane hemodialysis (HD) as an adjuvant treatment to standard chemotherapy for patients with acute kidney injury complicating multiple myeloma (MM) and its impact on further dialysis dependency. Methods 60 patients with acute dialysis-dependent renal failure secondary to MM were treated with MCO-HD (55 patients) or HCO (High Cut-Off)-HD (5 patients) as a control. FLC serum concentration, total protein, immunoglobulins and LDH were measured throughout the dialysis therapy. Patients' kidney function was followed for one year.Median age was 69 years; 25 female, 35 male patients were enrolled. HD significantly reduced FLC kappa levels in the MCO/HCO group by 58%/84% (MCO/HCO group; p < 0.05) and FLC lambda by 39%/33% (MCO/HCO group; p < 0.05). Single HD data (MCO) showed a relative reduction of 70 % in kappa and 37% in lambda FLC concentration, as expected by the different sizes of the light chains. Renal function improved significantly and continuously from starting creatinine 5.7/3.8 mg/dl (MCO/HCO group) before HD to 1.4/2.0 mg/dl (MCO/HCO group; p < 0.001) after one year. No significant alteration of total protein, immunoglobulins and LDH concentrations by HD (HCO and MCO group) was observed.After one year, 37 of 60 patients were alive and 34 of them were off dialysis.FLC elimination with MCO-HD is effective, technically easy and less cost-intensive as HCO-HD. Kidney function recovery in MM patients is achievable.